Adverse neurological events due to antiretroviral therapy in Mali (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
IntroductionAdverse neurological events during antiretroviral treatment (ART) are frequent and various1-3. Their diagnosis is difficult in developing countries where human resources and infrastructures are most of the time lacking.AimTo identify the frequency of neurological side effects in patients under ART in MaliMethodsWe performed a prospective cohort study on patients developing neurological symptoms  in a period of 12 months at the Department of Infectious Diseases of the Teaching Hospital “Point G” of Bamako, Mali. Neurological diagnostic was established with the guidance of a neurologist. WHO’s sides effects table has been used to characterize and classify the side effects4. Analysis of data was performed with SPSS Software, version 12.0.ResultsA total of 420 HIV seropositive patients under ART have been followed.  Of those, 37 cases were found with adverse neurological events (8.08%). The sex ratio M/F was 1.06 and. the mean age was 41.2 years. Of the side effects, polyneuritis alone represented 83.8% of the cases, and polyneuritis associated to vertigo, headache and depression represented the remaining 16.2 %. We didn’t notice any these neurological symptoms at the initiation of the ART. The majority of the patients was infected by HIV-1 (91.9 %). Most of the patients, 89.2% were treated with a fixed dose combination of Triomune® (D4T+3TC +Nevirapine).  Five cases were at 3rd stage of WHO classification (13.5%), which justified stopping the treatment with d4T.ConclusionsThe use of Triomune® led to neurological adverse events in Mali. Any further new antiretroviral regimens must include a pharmacovigilance to detect eventual neurological side effects.